Simulated African Swine Fever (ASF) virus detection in Italy: average numbers of farms and pigs under restriction - Giorgia Baiocchi; Andrea Marcon; Olivia Bessi; Luigi Ruocco; Vittorio Guberti (Veterinaria Italiana, 2023)
African swine fever is a devastating contagious viral disease of kept and wild porcine animals that will challenge the Veterinary Services involved in its eradication. Nowadays, ASF represents one of the biggest challenges for the pig sector at a global level. Following a number of simulated virus random introductions, the paper estimates the average number of farms (including their type) and animals that will be under restriction, and finally the average distance of infected farms from the nearest rendering plant. The study includes data referring to 101,032 farms with 9,322,819 pigs which are available in the Italian National Database (BDN). The simulations consider 5 different biogeographic regions with their own domestic pig distribution, breeding systems, and wild boar presence. Following an index case in a farm, and in the worst‑case scenario, in the 10 km radius of the restriction area, there will be: 2,636 farms in South Italy; 470,216 animals in Po Valley; 147 km in Central Italy is the longest mean distance from the infected farm to the nearest rendering plant.